Improving Public Health Awareness Through Free Health Check-ups at Sunan Giri University, Surabaya - Muhammad Farih Alfaaza (Institut Agama Islam Al-Fatimah Bojonegoro, 2024)
The free health event held at Sunan Giri University Surabaya aims to increase public awareness about the importance of routine health checks and providing easily accessible health services. This research uses a qualitative method with a case study approach. The main findings show that this program is effective in reducing barriers to access to health services, increasing public understanding of the importance of health checks, and providing useful education about disease prevention. The evaluation shows that the event was successful in meeting its objectives and highlights the need to continue and expand similar programs to reach wider community groups. This article contributes to filling the gap in research on community health programs by emphasizing the importance of the integration of free services and health education. The practical implications of this research include the development of broader outreach strategies and the use of digital technology to increase the reach and effectiveness of health programs in the future